Frontotemporal dementia with amyotrophic lateral sclerosis: A clinical comparison of patients with and without repeat expansions in C9orf72. Issue 3 (April 2013) - Snowden, Julie S.; Harris, Jennifer; Richardson, Anna; Rollinson, Sara; Thompson, Jennifer C.; Neary, David; Mann, David M. A.; Pickering-Brown, Stuart
Abstract Repeat expansions in C9orf72 are a major cause of frontotemporal dementia with amyotrophic lateral sclerosis (FTD-ALS). Not all FTD-ALS patients show expansions. The study examined whether there are clinical differences between FTD-ALS patients with and without expansions in C9orf72. We examined case notes from consecutive FTD-ALS patients, screened for C9orf72 expansions, and documented demographic, neurological, behavioural and cognitive characteristics. Sixty patients met the selection criteria, of whom 11 showed expanded repeats (C9-positive) and 49 did not (C9-negative). A strong male bias was present in the C9-negative group only. A family history of FTD or ALS was recorded in both groups, but was significantly more common in C9-positive cases. Psychotic and irrational behaviours, apathy, disinhibition and loss of empathy were significantly more common in C9-positive cases, with a trend towards more frequent bulbar signs. No differences were found in onset age, presentation (ALS or FTD first), or cognitive changes (language and executive impairments). In conclusion, FTD-ALS is not clinically uniform. Phenotypic differences exist between patients with and without C9orf72 expansions, suggesting that FTD-ALS may be underpinned by distinct neurobiological substrates. The presence of psychiatric symptoms in the context of FTD-ALS should alert clinicians to the possibility of C9orf72 expansions.